Hubungan Kinerja Karyawan Terhadap Kepuasan Konsumen Pada PT. Bess Finance Kota Metro - Nanto, Rocky; Wimbawani, Wiwik; Umar, M Abdullah (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
Customer satisfaction is a crucial element in the financial industry that affects customer loyalty. This study aims to examine the relationship between employee performance and customer satisfaction at PT Bess Finance Metro City. Involving qualitative and quantitative analysis techniques, this field research examined the independent variable (employee performance) and the dependent variable (customer satisfaction). Through an explanatory survey of 62 customers, data was processed to evaluate employee performance and customer satisfaction. Results showed a significant relationship between employee performance and customer satisfaction. Data collected from consumer respondents showed that there was a male dominance in the respondents, with the majority of BPKB motorcycle collateral users in the age range of 30 to 39 years. The frequency distribution of employee performance indicated the highest score in the 38 to 41 score range, while the lowest score was in the 50 to 53 range. Through Spearman Rank correlation analysis, a significant relationship was found between employee performance and customer satisfaction. The conclusion of this study confirms the positive relationship between employee performance and customer satisfaction. The higher the employee performance, the higher the level of customer satisfaction. The implication of this study shows the need for training and guidance for employees of PT Bess Finance Metro City to improve their performance in serving customers. This study provides limited insight into the population and sample at PT. Bess Finance Metro City, with the hope that it can be a source of development for further research.